Holistic Marketing Approach in Media Communications of Sports Organizations - Marija M. Jankovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
This paper will give theoretical and practical approaches to media communications in sport organizations. The first part of the paper presents theoretical aspects of media communications in sport organizations in history, by leading authors in the field of sport management. Modern sport communications range from traditional forms of experiences to an integrated, holistic approach, which includes information technology platforms, modern presentations of sport events, interactive discussion with audiences, by using social media. The second part of the paper will present theoretical aspects of sport journalism in the era of modern media communications. It is emphasised that all aspects of media communications have an impact on the leading of sport organizations and events. This paper emphasises that the new generation of sport audiences need integrated, modern approaches, based on both traditional and modern media communications, as well as a new approach to sport journalism.